Lot Streaming Flow Shop with a Heterogeneous Machine. Issue 2 (3rd April 2019) - Ferraro, Augusto; Rossit, Daniel; Toncovich, Adrián; Frutos, Mariano
Abstract: It is possible to obtain greater productivity of a production system by overlapping the operations required to process a manufacturing order. This methodology, known as lot streaming, requires dividing the production order (lot) into smaller sublots. In this article, we study production systems that include machines that operate in batch mode (processing a group of units at the same time) and single processing machines (processing one unit at a time) arranged in a flow shop configuration, that is all jobs must go through the same production stages in the same order. The obtained results show that addressing the problem with consistent sublots (a common sublot size used for the whole process) is inefficient. On the other hand, addressing the problem considering the sizing of sublots for each machine (variable sublots) greatly improves the quality of the solution but is computationally intensive (limiting the size of the problem that can be solved). Therefore, a decomposition procedure is proposed on the decision of sublots sizing. This procedure greatly improves the solution obtained using consistent sublots and does so with lower computational requirements than the variable sublots approach.